Emergent dynamics of light-induced active colloids probed by XPCS. (1st September 2022) - Zinn, Thomas; Narayanan, Theyencheri; Kottapalli, Sai Nikhilesh; Sachs, Johannes; Sottmann, Thomas; Fischer, Peer
Abstract: Self-propelled particulate systems manifest certain collective behavior of living matter, which have been the subject of intense research over the past decades. One of the elegant methods for realizing such active motions is by means of custom synthesized Janus particles suspended in a catalytic medium that can be triggered upon illumination by ultraviolet light. In this work, the evolution of the particle dynamics from passive diffusive to active ballistic behavior upon light illumination was probed by multispeckle x-ray photon correlation spectroscopy (XPCS). This technique enables not only studying the emergence of active motions in three dimensions (3D) but also deciphering different contributions to the overall dynamics. Using a combination of homodyne and heterodyne analysis, the ensemble averaged mean velocity, velocity fluctuations and diffusion coefficient of particles were determined in the thermodynamic limit. Results revealed a gradual transition from diffusive to ballistic dynamics with systematic increase of the catalytic activity. At the intermediate region, the dynamics is dominated by Gaussian velocity fluctuations and an enhanced relaxation rate with a weaker wave vector dependence similar to superdiffusive behavior. For the highest activity, the dynamics became purely ballistic with Lorentzian-like distribution of velocity fluctuations. Presented results demonstrate that different aspects of active dynamics can be investigated in 3D over a broad range of Péclet numbers and other control parameters by means of multispeckle XPCS.